Biomassa Bibit Tanaman Jambu Mete (Anacardium occidentale L.) yang Ditanam pada Tanah Pascatambang Emas Bombana dengan Variasi Pupuk Kandang - Ambardini, Sri (Al-Kauniyah: Jurnal Biologi, 2014)
Research to back up ex gold mining restoration must been done with productive plant so gets to answer about problem environmental one arises mining industry effect and can get to increase economy of plant exploit facet. This research aims was to know plant seed growth Cashew nut (Anacardium occidentale L.) with biomassa accumulation on organ comes to root, bar, and plant seed leaf of Cashew nut ( Anacardium occidentale L.) that old three-month after implant. Experiment research utilize fledged random design (RAL), consisting tree manures (crib manures, goat den manures, and henhouse manures) with same dose, which is 150 ha-1 tons, and control (without manures) with five replicated. Experimental procedure consisting of plant media preparation utilize ex mining land, preparation organic and an organic manure seed instilling, manuring, preserve, and cropping. Instilling and plant preserve is done in green house FMIPA UHO'S Biological. Result observationaling to point out that biomassa allocation plant tends to be presented at by leaf then bar organ and root, well on control and also on conduct by manures den. Biomassa allocation percentage in plant organ that is given manures greater crib than deep plant organ on conduct manures henhouse, goat den manure and control. Biomassa allocation most little on organ comes to root with percentage most little on conduct manures crib then on henhouse manure and supreme on goat den manure.